PENGEMBANGAN MEDIA PAPAN PINTAR DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V PADA MATERI KPK DAN FPB - Mirna watii; Jasiah (STKIP Subang, 2025)
ABSTRACT This research and development (R&D) study aims to develop and test the effectiveness of Smart Board media in improving fifth-grade students’ understanding of Least Common Multiple (LCM) and Greatest Common Factor (GCF). The development procedure follows a simplified Borg and Gall model consisting of preliminary research, planning, preliminary product development, expert validation, product revision, limited field testing, and final product refinement. This research was conducted at MIS Fathul Iman Palangka Raya with 30 fifth-grade students. Data were collected through expert validation sheets, a learning achievement test, and a student response questionnaire. The expert validation results indicated that the Smart Board media met the criteria of feasibility, clarity of use, and appropriateness for mathematics learning. During limited field testing, students used the media in groups to solve LCM and GCF problems and demonstrated active involvement and positive responses toward the media’s design and ease of manipulation. Learning achievement test results showed that most students achieved scores above the minimum mastery criteria, indicating improved conceptual understanding. Based on these findings, the Smart Board media is feasible and effective for supporting mathematics learning in elementary schools.